Resilience, Change Management, and Business Sustainability in the New Normal of the Selected PCAB-Accredited Companies - Polinar, Mark Anthony N.; Buntigao, John Lemuel G.; Cabatingan, Albim Y.; Delantar, Alexander Franco A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Amidst this global health pandemic, contractors are facing many challenges they never experienced before. With the widespread workplace changes, business sustainability has been in the spotlight. This descriptive-correlational-comparative research delved into resilience, change management, and business sustainability among the respondents of the selected PCAB-accredited contractors in Cebu City in 2022. The study's findings indicated that the respondents are very resilient, ready for change, and have a very positive note on business sustainability. The relationship between variables was shown in this paper, including the respondents' perceptions of the variables considered when grouped as officers and rank-and-file employees. The following conclusion is that even if the quantitative findings are on the higher end of the scale, more needs to be done to maintain them over a long period. Contractors must plan to be ready for any situation, even major disasters or unforeseen events. Making a crisis management strategy and business continuity dynamics will be very helpful for organizations. Additionally, the PCAB Contractors must be strong and resilient in times of unpredictability, complexity, ambiguity, and volatility to be ready for anything that may arise. To raise the levels of resilience, readiness for change management, and business sustainability among the staff of the chosen PCAB-registered construction enterprises in Cebu City, a thorough business continuity plan and business continuity dynamics were developed.